The European Digital Library – Factor for Long-life learning in Arts and Cultural Studies - Yankova, Ivanka; Velev, Evgeni; Nusheva, Kamelia; Spasova, Sonia (Qualitative and Quantitative Methods in Libraries, 2017)
The research paper examines the new opportunities arising for the Faculty of Library Sciences and Cultural Heritage in SULSIT, Bulgaria based on Project № FNI K 02/25(Contract № DFNI K 02/17)  „Developing a conceptual model for innovative educational, cultural and entertaining environment for personal and community development in the process of art and cultural education in lifelong learning.“  The purposes of the paper is to prove that the necessity for creating of specific analyses, visual investigations at site, evaluations is directly connected on one side with the improvement of the long-life learning in arts and cultural studies and on another side with the forming of personal and social integration of the individual and the social groups in the society.